Co-Operative Radical Pelvic Surgery: A Role for the Gynecologist in Vaginal Reconstruction Using a Uterine Myoserosal Flap in Urological and Anorectal Cancer Surgery. Issue 5 (1st June 2015) - Saadeh, Feras Abu; Cheema, Iwad; McCormick, Paul; Gleeson, Noreen
Abstract : Abstract: This study describes a new technique for reconstructing the vagina and vestibule after radical extirpative surgery for urological and anorectal malignancy. The uterus is always excised when exenterative surgery is performed for gynecological cancer. The use of the uterus as a graft gives the gynecologic oncologist/reconstructive surgeon a role in the multidisciplinary team with urologists when the anterior vaginal wall and vestibule are excised and with the anorectal surgeons when the posterior vaginal wall and perineum are excised for nongynecological cancers. In some such cases, only the anterior or posterior wall of the vagina may be excised, leaving a healthy full-length, one-third, or half-circumference vaginal sleeve. A myoserosal flap is raised from the in situ uterus. The ectocervix is excised, and the adnexa are detached or excised. The uterus is opened to generate a hexagonal flap. The endometrium and endocervix are excised/ablated with electrocautery. The flap is advanced to the edge of the remaining anterior vestibule or reconstituted perineum. The serosal surface of the uterus forms the new wall of the vagina and undergoes metaplastic transformation to squamous epithelium within 3 months. The very satisfactory anatomical and functional outcome means that this technique merits further evaluation.